Analyzing Cognitive Styles and Spatial Abilities in Geometry Transformations through the Problem-Based Learning Approach - Syahbudin, Fauzan; Priatna, Nanang; Yulianti, Kartika (FKIP Universitas Lampung, 2024)
Analyzing Cognitive Styles and Spatial Ability in Geometry Transformations Learning through PBL Approach. Objective: This study aims to investigate the spatial abilities of grade IX junior high school students using the Problem- Based Learning (PBL) approach, considering their cognitive styles: Field Independent (FI) and Field Dependent (FD). Methods: Using a descriptive qualitative approach, six students were selected based on their cognitive styles and spatial ability. Data were collected through spatial ability tests, interviews, and classroom observations. Findings: The findings highlight notable differences in spatial abilities between FI and FD students. FI students displayed strengths in spatial visualization, perception, and orientation, excelling in tasks that required analytical problem-solving and independent work. However, they faced challenges in mental rotation and proportional scaling during dilation, often struggling with complex transformations due to limited exposure and insufficient time management. FD students performed better in structured tasks, particularly spatial perception and orientation, benefiting from guided instructions and peer support. Nevertheless, FD students encountered significant difficulties in mental rotation and spatial relations, particularly in tasks requiring independent conceptual understanding. Group dynamics played a crucial role in the effectiveness of PBL. Balanced groups, consisting of both cognitive styles, fostered collaboration and improved learning outcomes. In contrast, homogeneous or imbalanced groups often resulted in reduced engagement and lower performance.Conclusion: This study underscores the necessity of adapting PBL strategies to align with the distinct needs of cognitive styles. FI students thrive with opportunities for independent exploration and structured individual feedback, while FD students require collaborative, guided discussions and supportive group settings. By integrating differentiated instructional strategies, educators can optimize spatial ability development and ensure equitable learning opportunities for all students. These insights provide a framework for enhancing geometry education through targeted, inclusive approaches. Keywords: cognitive styles, field dependent, field independent, problem-based learning, spatial ability.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024144